Peak expiratory flow rate; the effect of smoking on younger & middle aged males - Satyanarayana, B.; Reddy, V. Devendar; Syamala, E. (International Journal of Research in Medical Sciences, 2017)
A total of 80 male subjects in age group of 20-50 years were selected for the purpose of the study. They were divided in two groups, smokers and non smokers. Each group subdivided into age groups of 20-35 and 36-50 yrs. The criteria for smoking was about 5-10 cigarettes per day since 6-12 months. Peak Expiratory Flow Rate (P.E.F.R.) was determined by using Wright’s peak flow meter. The results showed that in Non-Smoker of age group 20-35 years, (n= 30) the mean PEFR value was 535±50 L/min, whereas in age group 36-50 years, (n=15) the mean P.E.F.R value was 515±50 L/min. In Smokers of age group 20-35 years, (n=10) mean P.E.F.R. value was 374±128 L/min whereas in age group 36-50 years, (n=25) mean P.E.F.R. value was 357±86 L/min. This shows that in smokers P.E.F.R. value is lower compared to Non-smokers in both age groups and that P.E.F.R. is lower in the elder age group in comparison to younger age group.